1992
DOI: 10.1177/019262339202000209
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Promoting Effects of Both Iodine Deficiency and Iodine Excess in the Rat Thyroid

Abstract: A B S T R A~Thyroid tumor-promoting effects of iodine deficiency and iodine excess were investigated in a rodent 2-stage model to estimate an optimal iodine intake range that would not effectively promote development of thyroid neoplasia. Six-week-old male F344 rats were given a single subcutaneous injection of 2,800 mg/ kg body weight N-bis(2-hydroxypropyI)-nitrosamine (DHPN) or saline vehicle, maintained on Remington's iodine-deficient diet (21 k 2 ng/g iodide), and supplemented with various amounts of potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 44 publications
(37 reference statements)
3
36
0
1
Order By: Relevance
“…The precise factors that might explain the suggested risk of thyroid cancer associated with fish consumption have not been precisely determined, although dietary iodine is probably involved (Williams et al, 1977;Kanno et al, 1992). Iodine intake is probably higher in the northern parts of Norway, and an estimation of the intake based on consumption of fish and milk from 1983 to 1985 suggests a ratio of 1.5 between northern Norway and east Norway (K Lund-Larsen, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The precise factors that might explain the suggested risk of thyroid cancer associated with fish consumption have not been precisely determined, although dietary iodine is probably involved (Williams et al, 1977;Kanno et al, 1992). Iodine intake is probably higher in the northern parts of Norway, and an estimation of the intake based on consumption of fish and milk from 1983 to 1985 suggests a ratio of 1.5 between northern Norway and east Norway (K Lund-Larsen, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments J. Kanno et al (28) have shown that iodine in the diet contributes to the occurrence of thyroid neoplasia in a special way. The curve showing the percentage of rats with lesions is bimodal with one peak in the low range of iodine intake, that is approximately 1-10 µg/rat/day, and one in the range from around 1000 µg/rat/day and upwards.…”
Section: Viewpoints On Thyroid Carcinogenesismentioning
confidence: 99%
“…According to epidemiological, clinical and experimental studies, both the dietary deficiency and excess of iodine have been associated with increased risk of thyroid carcinomas [5][6][7][8] . In this connection, the effect of salt water fish and shellfish consumption as a measure of iodine exposure has been discussed [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%